2016
DOI: 10.5194/angeo-34-271-2016
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of deformed ionograms induced by vertical ground motion of seismic Rayleigh waves and infrasound in the thermosphere

Abstract: Abstract. The vertical ground motion of seismic surface waves launches acoustic waves into the atmosphere and induces ionospheric disturbances. Disturbances due to Rayleigh waves near the short-period Airy phase appear as wavy fluctuations in the virtual height of an ionogram and have a multiple-cusp signature (MCS) when the fluctuation amplitude is increased. An extremely developed MCS was observed at Kazan, Russia, after the 2010 M 8.8 Chile earthquake. The ionogram exhibited steep satellite traces for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
(24 reference statements)
1
19
0
2
Order By: Relevance
“…4). Recently, Maruyama et al (2016) have observed the deformation in the lower-frequency edge of the ionograms at the time of the arrival of the seismic infrasound in the ionosphere. They have also reported the ionospheric perturbations in the height range below 200 km.…”
Section: Ionospheric Response To Seismic Infrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Recently, Maruyama et al (2016) have observed the deformation in the lower-frequency edge of the ionograms at the time of the arrival of the seismic infrasound in the ionosphere. They have also reported the ionospheric perturbations in the height range below 200 km.…”
Section: Ionospheric Response To Seismic Infrasoundmentioning
confidence: 99%
“…On the other hand, many investigations have reported the ionospheric perturbations to remain confined to the bottom of the F layer (e.g. Chum et al, 2012;Maruyama et al, 2016). Likewise, different researchers have proposed different modes of acoustic propagation.…”
Section: Introductionmentioning
confidence: 99%
“…One of these phenomena is generation of midscale ionospheric irregularities directly by shock wave from the supersonic seismic source propagating over the surface [ Maruyama et al , ; Liu et al , ; Rolland , ; Kakinami et al , ; Maruyama and Shinagawa , ; Berngardt et al , ; Maruyama et al , , ; Kherani et al , ; Chum et al , ; Liu et al , ]. These irregularities are observed at ionograms as fast changes of the trace over frequency and time (initially smooth and slow changing) and known as multicusp effect [ Maruyama et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…For study of the multicusp vertical ionosondes are widely used [ Maruyama et al , ; Maruyama and Shinagawa , ; Maruyama et al , , ]. The use of chirp ionosondes for monitoring tasks allows us to easily increase sweep speed and increase the time resolution of the ionosonde.…”
Section: Introductionmentioning
confidence: 99%
“…Rayleigh wave signatures in the ionosphere following earthquakes have been measured by Doppler sounding (e.g., Yuen et al 1969;Tanaka et al 1984;Artru et al 2004;Chum et al 2016) using TEC measurements (e.g., Ducic et al 2003;Astafyeva et al 2009;Rolland et al 2011) and the inspection of ionograms (Maruyama et al 2012(Maruyama et al , 2016a(Maruyama et al , 2016b.…”
Section: Introductionmentioning
confidence: 99%